Pengaruh Budaya Organisasi, Gaya Kepemimpinan, Dan Pelatihan Terhadap Loyalitas Karyawan Di Era Transformasi Digital - Cecep Ridwan (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the influence of organizational culture, leadership style, and training on employee loyalty in the era of digital transformation. The research was conducted by Cecep Ridwan in 2026 as part of the Management Study Program at the Faculty of Economics and Business, Pelita Bangsa University, Karawang. The study focuses on internal company factors that affect employee loyalty amid changes in the work environment driven by digital transformation. Digital transformation has significantly changed business operations, work systems, communication patterns, and employee competency requirements. Companies are required to adapt quickly to remain competitive. These changes demand employees to continuously develop their skills and adjust to new technologies. Poor change management can lead to decreased employee loyalty. Employee loyalty is crucial because it affects organizational stability, productivity, and long term sustainability. Organizational culture plays an important role in shaping employee loyalty. It reflects shared values, norms, and behaviors within the company. A strong and clear organizational culture can create a sense of belonging and commitment among employees. In the digital era, organizational culture must support innovation, openness, and continuous learning to encourage employee engagement and loyalty. Leadership style also influences employee loyalty. Leaders who are adaptive, supportive, and able to guide employees through change can increase trust and commitment. Effective leadership helps employees feel motivated and aligned with organizational goals during periods of transformation. Training is another key factor affecting employee loyalty. Digital transformation requires employees to acquire new skills relevant to technological developments. Training programs help improve employee competence and readiness. Employees who receive training opportunities tend to feel valued, which increases job satisfaction and encourages them to remain with the company. This research uses a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to employees in companies implementing digital transformation. Multiple linear regression analysis was used to measure the effect of organizational culture, leadership style, and training on employee loyalty. The results are expected to show that organizational culture, leadership style, and training have a positive effect on employee loyalty. The findings can be used as a reference for company management in developing effective human resource strategies to maintain employee loyalty in the digital transformation era.